Safety and diagnostic performance of pulmonologists performing electromagnetic guided percutaneous lung biopsy (SPiNperc). Issue 5 (24th January 2019) - Mallow, Christopher; Lee, Hans; Oberg, Catherine; Thiboutot, Jeffrey; Akulian, Jason; Burks, Allen C.; Luna, Branden; Benzaquen, Sadia; Batra, Hitesh; Cardenas‐Garcia, Jose; Toth, Jennifer; Heidecker, Jay; et al.
ABSTRACT: Background and objective: Percutaneous lung biopsy for diagnostic sampling of peripheral lung nodules has been widely performed by interventional radiologists under computed tomography (CT) guidance. New technology allows pulmonologists to perform percutaneous lung biopsies using electromagnetic (EM) guided technology. With the adoption of this new technique, the safety, feasibility and diagnostic yield need to be explored. The goal of this study was to determine the safety, feasibility and diagnostic yield of EM‐guided percutaneous lung biopsy performed by pulmonologists. Methods: We conducted a retrospective, multicentre study of 129 EM‐guided percutaneous lung biopsies that occurred between November 2013 and March 2017. The study consisted of seven academic and three community medical centres. Results: The average age of participants was 65.6 years, BMI was 26.3 and 50.4% were females. The majority of lesions were in the right upper lobe (37.2%) and left upper lobe (31.8%). The mean size of the lesions was 27.31 mm and the average distance from the pleura was 13.2 mm. Practitioners averaged two fine‐needle aspirates and five core biopsies per procedure. There were 23 (17.8%) pneumothoraces, of which 16 (12.4%) received small‐bore chest tube placement. The diagnostic yield of percutaneous lung biopsy was 73.7%. When EM‐guided bronchoscopic sampling was also performed during the same procedural encounter, the overall diagnostic yield increased to 81.1%. Conclusion: In this large multicentred series, the use of EM guidance for percutaneous lung biopsies was safe and feasible, with acceptable diagnostic yield in the hands of pulmonologists. A prospective multicentre trial to validate these findings is currently underway (NCT03338049). Abstract : Lung cancer screening has led to the discovery of over 1 million pulmonary nodules each year. New technology allows pulmonologists to perform percutaneous lung biopsies using electromagnetic (EM) guided technology. In this retrospective analysis, we demonstrate that EM percutaneous needle biopsy is safe, feasible and provides an acceptable diagnostic yield. See related Editorial